DAMPAK PROMOSI TERHADAP TINGKAT PENJUALAN KACAMATA DI OPTIK KABUPATEN KAMPAR RIAU - Wesnita, Alvia; Pascaselnofra Amril, Alwa; Corina, Febry; Okto Randi, Peni (Ensiklopedia of Journal, 2024)
With the increasing growth of optics in various regions, the competition is getting sharper. One of the activities that is often carried out is to carry out promotional activities. Through this promotional activity, Optical tries to introduce their superior products to consumers, then persuade potential customers to buy the products they offer. The model or method that will be used in this research is a quantitative descriptive method. This method was chosen because the research process carried out by researchers was by conducting interviews and distributing questionnaire sheets to all customers. Promotional strategies using social media increase sales by 80%. 2. Promotional strategies using print media such as catalogs, brochures and banners can increase sales by 83%. Promotion using social media can increase eyeglass sales by 80% and using print media can increase eyewear sales by 83%. Social media reaches potential consumers very easily, but potential consumers cannot directly choose the product they want. Print media shows product descriptions directly to potential customers, so that potential customers can directly choose the product they want.Keywords: Promotion, Sales Level, Optics.